THE EFFECTIVENESS OF THE SUPERVISORY FUNCTION OF THE IMPLEMENTATION PROCEDURES IN NORTH SULAWESI PROVINCE REGIONAL INSPECTORATE - LASIRO, MEYCHAEL; RORONG, ARIE; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2019)
The purpose of the research is to find out the effectiveness of the procedure for the implementation of the supervisory function in the Insperktorat area of North Sulawesi province. This research uses qualitative approach method. Research Informant was the person the Inspector, 2 person head of Sub-Division, 2 person Irban Region 5 Office/Bureau of Associated, in total as many as 10 informants. Data collection using the guidelines of the interview, while the analysis techniques used are interactive model analysis from Miles and Hubernan. Based on the results of the data analysis is drawn the conclusion: (1) organizational Productivity or output in this case regarding the work of the regional Inspectorates North Sulawesi province in the exercise of supervisory functions in eithercase showed where the work given that ability is in compliance with the employees of the Inspectorate and owned the purpose of supervision. So as a result it works or output is also satisfying for the Bureau/Office/field as an objects of supervision. (2) the effectiveness of the Organization in the form of his success adapting to changes inside and outside the Organization has been very good. This is evident from the adaptability of the inspector’s staff with work and organization environments that is very good as well as in carryng out the supervision procedures in accordance with the tupoksi and existing standard operating procedures. (3) the absence of tension within the organization or obstacles to conflict among parts of the organization. In this case it can be seen that the relationship between the imployee of the inspectorat and his superiors as well as colleagues/co-works is well established as well as the attitudes and relationships shown to the agency/bureau/field of supervision of the inspekto’s staff.Keywords: Effectiveness , Implementation, Supervision